Differential effects of S-allyl cysteine and cannabidiol on enterocytic and plasma amyloid-β in db/db diabetic mice - Arazu Sharif; Maimuna Majimbi; John Mamo; Virginie Lam; Michael Nesbit; Ryu Takechi (Scientific Reports)
Abstract Peripheral amyloid-beta (Aβ), including those in bloodstream and intestine, is implicated in the pathogenesis of Alzheimer’s disease (AD). Additionally, diabetes and insulin resistance are associated with the impairment of Aβ metabolism and an increased risk of developing cognitive decline and AD. Previous research has demonstrated the neuroprotective effects of cannabidiol (CBD) and S-allyl-cysteine (SAC); however, their impact on Aβ levels in the context of diabetes remains unexplored. 5-week-old diabetic db/db mice underwent 23 weeks of dietary interventions with SAC, CBD, or a combination of SAC and CBD. Immunofluorescent imaging quantified enterocytic Aβ abundance and plasma concentrations of Aβ42, Aβ40, and Aβ oligomers were measured using ELISA. Our results reveal a progressive increase in enterocytic Aβ expression in db/db mice, which was mitigated by SAC administration. In contrast, CBD treatment alone and in combination with SAC, increased enterocytic Aβ abundance and elevated plasma Aβ42 concentrations. The combination therapy reduced Aβ oligomers. These findings suggest that the neuroprotective effects of SAC are partially mediated by its impact on peripheral Aβ levels. CBD could potentially exacerbate Aβ accumulation in diabetes.